Balancing of 3-rpr planar parallel robots passing through singular configurations - Süülker, Cem (My University, 2018)
Paralel robotlar, seri muadillerine kıyasla birtakım üstünlüklere sahiptir, ve bu nedenle sanayide yaygın bir şekilde kullanılırlar. Bu robotlara özgü Tip II tekillik problemi literatürde geniş ölçüde çalışılmıştır. Genel itibariyla gereken eyleyici kuvvetleri bu tekil konfigurasyonlar civarında sonsuza ıraksar, ve robotun kontrol edilebilirliği kaybolur. Tekilliklere karşı gürbüz dengeleme yöntemi Tip II tekilliklerden geçmek için geliştirilen en son metotlardan biridir. Literatürdeki hareket planlama yöntemleri istenen herhangi bir yörüngeyi takip etmede yardımcı olamaz, ancak tekilliklere karşı gürbüz dengeleme yöntemi ile bütün yörüngeler gerçeklenebilir. Bu tezde, tekilliklere karşı gürbüz dengeleme yöntemi, her bir bacağa birer tane sabitlenmek suretiyle, üç karşı ağırlık kullanarak 3-RPR düzlemsel paralel robotlara uygulanmıştır. Denge tasarım denklemi çıkarılmış ve karşı ağırlıkların uygun konumları analiz edilmiştir. Bu kapsamda iki teorem ve iki sonuç teoremi verilmiş ve ispatlanmıştır. Teorik olarak elde edilen sonuçlar sayısal örneklerle de doğrulanmıştır. Bu amaçla farklı dengeleme senaryoları incelenip biribiryle karşılaştırılmıştır. Dengeleme parametrelerinin robotun performansı üzerindeki etkisi, eyleyici kuvvetlerinin azaltılmasına dayanan bir performans indeksini baz alarak tartışılmıştır.

Parallel robots offer a number of superiorities over their serial counterparts, and for this reason they are widely used in industry. Type II singularity problem that is characteristic to these robots has been studied extensively in the literature. In general, the required actuator forces grow unboundedly around these singular configurations, and controllability of the robot is lost around them. The singularity robust balancing method is one of the recent methods that has been developed for crossing Type II singularities. Motion planning methods in the literature cannot help to track an arbitrarily desired trajectory; however, by using this recent method, every trajectory is realizable. In this thesis, the singularity robust balancing method is applied to 3-RPR planar parallel robots by using three counterweights, each being fixed to one separate leg. The balance design equation is obtained and suitable loci of counterweights are analyzed. Two theorems and two corollaries are given and proved within this context. The theoretical findings are also validated through numerical examples. Different balancing scenarios are considered and compared for this purpose. The effects of balancing parameters on the performance of the robot are discussed by considering a performance index that is based on decreasing the actuator efforts.
Keywords: Control systems; Denetim sistemleri; Hareket; Makine mühendisliği; Mechanical engineering; Motion; paralel robotlar; parallel robots; robotik; Robotlar; Robots; singularity; tekillik Robotics